Online Extremism and Terrorism Research Ethics: Researcher Safety, Informed Consent, and the Need for Tailored Guidelines - Conway, Maura (Terrorism and political violence, 2021)
This article reflects on two core issues of human subjects’ research ethics and how they play out for online extremism and terrorism researchers. Medical research ethics, on which social science research ethics are based, centers the protection of research subjects, but what of the protection of researchers? Greater attention to researcher safety, including online security and privacy and mental and emotional wellbeing, is called for herein. Researching hostile or dangerous communities does not, on the other hand, exempt us from our responsibilities to protect our research subjects, which is generally ensured via informed consent. This is complicated in data-intensive research settings, especially with the former type of communities, however. Also grappled with in this article therefore are the pros and cons of waived consent and deception and the allied issue of prevention of harm to subjects in online extremism and terrorism research. The best path forward it is argued—besides talking through the diversity of ethical issues arising in online extremism and terrorism research and committing our thinking and decision-making around them to paper to a much greater extent than we have done to-date—may be development of ethics guidelines tailored to our sub-field.